Effect of an Aspergillus Meal Prebiotic on Salmonella Infection in Turkeys and Broiler Chickens - Londero, A.; Menconi, A.; Reginatto, A.R.; Bacocina, I.; Wolfenden, A.; Shivaramaiah, S.; Hargis, B.M.; Tellez , G. (International Journal of Poultry Science, 2011)
The objective of this study was to evaluate the effect of 0.2% dietary Aspergillus Meal (AM) against horizontal transmission of Salmonella sp. in turkeys and chickens. Experiment 1 evaluated the effect of AM against horizontal transmission of Salmonella Enteritidis (SE) in turkeys. Day-of-hatch turkeys were assigned to untreated control or AM prebiotic-fed groups. Five additional seeder turkeys per group were challenged with 1.5 x 105 cfu SE and placed in each of the treatment groups 24 h later. At ten, twenty and thirty days of age, Cecal Tonsils (CT) were cultured for SE recovery. A significant reduction in SE recovery (25%, 30% and 35% respectively) was observed in prebiotic-fed turkeys when compared with controls (p